A Pastoral da Pessoa Idosa e os desafios do diálogo inter-religioso: a experiência na Arquidiocese de São Paulo - Carvalho, Conceição Aparecida de (2024)
In light of knowledge in the area of Science of Religion and in light of the Pastoral Care of the Elderly (PPI), the present work aims to carry out a study of the challenges of Inter-Religious Dialogue and the experience in the Archdiocese of Sao Paulo. Identify, in the universe of its episcopal regions, whether there is religious diversity among the elderly people visited. Using this knowledge, contribute to the training of Pastoral volunteers for interreligious dialogue. Firstly, we address the preferential option for the poor, one of the outstanding records of the Latin American Church, with gradual awareness from the Second Vatican Council to Pope Francis, reaching its peak in the CELAM Conferences. In a second moment, we mention the Social Pastorals in Brazil, elderly people and the work of the National Pastoral, the Archdiocese of Sao Paulo and the episcopal regions. In a third moment, we deal with the theme of religious diversity, religious pluralism and interreligious dialogue. Finally, challenges of interreligious dialogue for the Pastoral Care of the Elderly were noted; the diversity of the elderly people visited, the pastoral agents, the challenges. The results of the present study indicate that there is religious diversity among the elderly people visited by the PPI in their episcopal regions, with the exception of the regions of Santana and Brasilândia, in which they profess the Catholic faith. Based on this information, train Pastoral volunteers for interreligious dialogue